The Social Construction of Scabies Disease Among Islamic Boarding School Students - Suryanto, Totok Agus; Ladylie, Ladylie (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
The social construction of scabies among Islamic boarding school students (santri) is a critical yet underexplored issue. Previous studies have not fully addressed how scabies is perceived and constructed within this community. This study focuses on understanding the meanings and social interactions surrounding scabies among santri. Using a qualitative exploratory descriptive approach, data were collected through participant observations, in-depth interviews, and documentation studies. Analysis involved data interpretation, display, and conclusion withdrawal, guided by Berger and Luckmann's theory of social construction, which includes externalization, objectivation, and internalization. The findings reveal diverse meanings attached to scabies among santri, including